The risk factor of urinarytract infection in patient with leukemia - Melati Dini Hari, Soetaryo, Pungky Ardani Kusuma (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Urinary tract infection (UTI) is one of most common infectious diseases in patients wuth leukemia. Some researchers showed that the prevalence of UTI was the third highest after pneumonia and gastrointestinal tract infection among children with leukemia. UTI may be affected by many factors, i.e. host, microorganism, and environment. E. coli, Klebsiella, dan Proteus are the most common bacterial etiology of UTI in leukemia. Objective: The aim of this research was to know the risk 'factor of UTI in children with leukemia. Method: This research used case-control design. Subjects of this study were children (0-15 years old) with leukemia who came to Department of Pediatrics, Dr. Sardjito Hospital since January st, 2000 until October 3